Unfolding principles for student peer feedback: A comparative analysis across higher education contexts - Ellegaard, Marianne; Niss, Martin; Bruun, Jesper; Lämsä, Joni; Christiansen, Frederik Voetman; Linell, Gry Green; Larsen, Camilla Fogh; Nyman, Rimma; Johannsen, Bjørn Friis (Högre utbildning, 2022)
In this paper we conceptualize formative peer feedback principles by analyzing and comparing six empirical examples of formative peer feedback in a set of international STEM (science, technology, engineering, and mathematics) contexts. By discussing how these different approaches to peer feedback unfold in practice, we aim to facilitate the bridging of the gap between theory and practice in implementing peer feedback in Higher Education. As a group of researchers and teaching practitioners from six Higher Education institutions, we discussed, analyzed, and synthesized practical examples of peer feedback in STEM that cover a breadth of settings, aims, and forms. The analysis and comparison of these examples illustrate how principles in peer feedback emerge in practice. We discuss how the context in peer feedback influences its practical implementation, particularly with regard to its purpose and aims, the development and use of assessment criteria, and embedding and supporting the initiatives into the teaching and learning activities.